2004
DOI: 10.1310/jkjk-n2mp-9lq1-ff2n
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Education Materials on the World Wide Web: An Evaluation of Their Quality and Suitability

Abstract: Web-based information is a valuable resource for people affected by stroke, however its accuracy and quality have been questioned. In this study, 30 stroke education websites were reviewed using accountability, readability, and reliability measures. Fifteen consumers and 11 health professionals evaluated six sites in terms of their design, content, and ease of use. The websites mostly met accountability criteria, but their reliability scores were low and their readability was high. Consumers' opinions were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…Only two websites (5%) were written at 5 th grade or lower level. This result is consistent with previous studies, which evaluated some stroke-related web pages: The mean readability level of stroke information was found to be 10th grade in Griffin, McKenna, & Worrall's [41] evaluation of 30 stroke educational websites; these websites are different from the set of websites appraised in our study, except three overlapping websites. Sharma et al [22] also found that over half of 100 stroke Web pages were produced at the 12th-grade level or above when readability was measured with SMOG.…”
Section: Readabilitysupporting
confidence: 91%
“…Only two websites (5%) were written at 5 th grade or lower level. This result is consistent with previous studies, which evaluated some stroke-related web pages: The mean readability level of stroke information was found to be 10th grade in Griffin, McKenna, & Worrall's [41] evaluation of 30 stroke educational websites; these websites are different from the set of websites appraised in our study, except three overlapping websites. Sharma et al [22] also found that over half of 100 stroke Web pages were produced at the 12th-grade level or above when readability was measured with SMOG.…”
Section: Readabilitysupporting
confidence: 91%
“…Content could be perceived differently between health professionals and consumers. 5 Interviews with e-health consumers would be an interesting complementary approach to test the suitability of the websites information.…”
Section: Incomplete or Unspecific Correctmentioning
confidence: 99%
“…One of the few studies Revista Científica da Ordem dos Médicos www.actamedicaportuguesa.com assessing the quality of stroke education materials available on the web found high readability scores but poor reliability. 5 Although Portuguese literacy levels have increased tremendously in the last few decades, they are still lower than the European average, and it is estimated that 5% of adults and youth are still unable to read or write. 6 Literacy is an important determinant of access to healthcare and health information.…”
Section: Introductionmentioning
confidence: 99%
“…The readability levels of stroke education websites (n=50) have also been found to be inappropriately high (Griffin, McKenna and Worrall, 2004).…”
Section: Web Accessibilitymentioning
confidence: 99%